2016
DOI: 10.1167/iovs.15-18681
|View full text |Cite
|
Sign up to set email alerts
|

Subretinal Transplantation of Embryonic Stem Cell–Derived Retinal Pigment Epithelium for the Treatment of Macular Degeneration: An Assessment at 4 Years

Abstract: Advanced macular degeneration is an important cause of vision loss in the United States with over 2 million people affected by the disease. Despite substantial progress in the development of new therapies for wet AMD, the severe visual impairment associated with geographic atrophy in dry AMD or Stargardt disease remains untreatable. Recently, two phase I/II studies involving 18 patients with these diseases have demonstrated that it is possible to safely implant human embryonic stem cell-derived RPE (hESC-RPE) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
150
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(162 citation statements)
references
References 53 publications
1
150
0
11
Order By: Relevance
“…In agreement, preliminary data from the first clinical trial on hESC-RPE showed presence of pigmented tissue at the border of the atrophic area in GA patients. 1,29 Therefore, for the suspension approach to be functionally effective, it will most likely be crucial to choose patients diagnosed in an early stage of the disease, with a relatively conserved outer retina. The large-eyed GA model presented in this study should be a valuable tool for further understanding if and when hESC-RPE-based treatments may succeed in a clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement, preliminary data from the first clinical trial on hESC-RPE showed presence of pigmented tissue at the border of the atrophic area in GA patients. 1,29 Therefore, for the suspension approach to be functionally effective, it will most likely be crucial to choose patients diagnosed in an early stage of the disease, with a relatively conserved outer retina. The large-eyed GA model presented in this study should be a valuable tool for further understanding if and when hESC-RPE-based treatments may succeed in a clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Schwartz et al [85] reported the possibility of hESC-RPE to treat patients with Stargardt's macular dystrophy and dry AMD and provided preliminary data. Recently, 2 phase I/II studies with a length of 4 years, involving 18 patients with dry AMD or Stargardt's disease, demonstrated the possibility of safe implantation of hESC-RPE subretinally in an attempt to rescue photoreceptors and vision [86] .…”
Section: Cell Therapymentioning
confidence: 99%
“…In the clinical procedures described above, the subretinal injections of the hESC-RPE reported by Schwartz et al [85,86] were preformed along the site of a pars plana vitrectomy, and the injection sites were carefully chosen on the basis of optical coherence tomography results. Sites with native, albeit compromised, RPE and similarly compromised overlaying photoreceptors were thought to be the optimal injection spots for transplantation.…”
Section: Approaches For Subretinal Injectionmentioning
confidence: 99%
“…The RPE is important for photoreceptor survival and function, and loss of this cell type is involved in the pathophysiology of atrophy in AMD [65]. The rationale for transplantation of RPE cells is clear and the potential for cell-based therapy has been investigated in both animals and humans [66,67,68]. …”
Section: Induced Pluripotent Stem Cell-derived Retinal Pigment Epimentioning
confidence: 99%